Evaluation of anti-corrosion properties of DLC coatings for medical devices - Eraj Humayun Mirza; Syed Fahad Akbar Ali; Muhammad Asif; Wan Mohd Azhar, Ibrahim; Syed Najam ul Hassan (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/